CALCULATION OF SHORT RANGE ORDERING IN Ni-Ti ALLOYS - Abbas, Tahir; Khalil, R. M. Arif; Rana, A. M.; Mehtab-Ullah, (Journal of Research (Science), 2005)
The concentration dependence of atomic short range order(SRO) was studied in the Ni100-xTix(x=2,5,10 ,15,20,25,35,50 at.%) alloys using the frame work of the transition metal model pseudopotential (TMMP). The ordering energies and SRO parameters were calculated for Ni-Ti alloys. It was observed that this model predicted the correct sign of the SRO parameters for Ni-Ti alloys.